The Adaptive Immune Response in Graves’ Disease: Does Vitamin D have a role? - Purnamasari, Dyah; Soewondo, Pradana; Djauzi, Samsuridjal (Journal of the ASEAN Federation of Endocrine Societies, 2014)
Graves’ disease (GD) is an autoimmune disease characterized by excessive autoantibody formation by the lymphocyte B cells (B cells). The autoantibodies will bind to Thyroid Stimulating Hormone receptors (TSHR) and enhance the production of thyroid hormone. Previous studies indicate that the impairment of immune response in GD happens in several points in the adaptive immune response, particularly the profile of the intrathyroidal dendritic cells (tDC), the imbalance of T helper-1 (Th1) and T helper-2 (Th2), the Th17 cells that act as pro-inflammatory cells and the dysfunction of immune modulating T regulator (Treg) cells.6-11 Vitamin D is a steroid hormone which has pleiotropic effects. The role of vitamin D in bone and calcium metabolism is already established. The discovery of vitamin D receptor (VDR) in immune cells such as monocytes/macrophages, T cells and B cells, demonstrates that vitamin D may influence innate and adaptive immune process. Recent studies try to explore the relationship between vitamin D and autoimmune disease, furthermore they consider vitamin D as a modifiable environmental factor in autoimmune diseases.13,40 Most people with autoimmune diseases have lower vitamin D level than that of healthy subjects. Vitamin D level also has been associated with disease activity of Systemic Lupus Erythematosus (SLE) and Rheumatoid Arthritis (RA). Vitamin D influences adaptive immune response through its ability to modulate dendritic Cells (DC), T cells, B cells and Treg cells. Although previous studies reported the immune response disturbance in GD include the tDC, Thelper and Treg cells,6-11 little is known whether the immunoregulatory effect of vitamin D can interfere with the natural history of GD. The effect of vitamin D in GD remains to be explored.